PENINGKATAN HASIL BELAJAR MUATAN IPS DALAM PEMBELAJARAN JARAK JAUH DENGAN MENERAPKAN PERMAINAN OPEN THE BOX SISWA KELAS IV SDN 2 KALIREJO - Faroh, Nisrina Nurul (CV Sintesia, 2024)
The objectives of this study are: (1) to apply open the box games to improve social studies learning outcomes for fourth grade students at SDN 2 Kalirejo in the 2020/2021 academic year and (2) to improve social studies learning outcomes for fourth grade students at SDN 2 Kalirejo in the 2020/2021 academic year through the application of open the box game.This research is a classroom action research (CAR). The research was carried out in two cycles, each cycle consisting of 6 meetings. This research was carried out in four stages consisting of planning, implementation, observation and reflection. The subjects of this study were fourth grade students of SD Negeri 2 Kalirejo. The data sources of this research are teachers, students, and documents. Data collection techniques using tests and observations. Data analysis used is qualitative data analysis techniques and quantitative data analysis. The results of this study indicate that: (1) the application of open the box games to improve social studies learning outcomes for grade IV SDN 2 Kalirejo for the academic year 2020/2021 is carried out through five steps, namely: (a) delivering material using power points; (b) random selection of students using a random wheel; (c) selected students answer the questions in the box and other students are given the opportunity to express their opinion; (d) giving rewards for students who successfully answer and dare to have an opinion; (e) the teacher provides feedback. The results of the observations indicate that the research was carried out in accordance with the steps that have been prepared well (2) the application of open the box games has an effect on increasing student learning outcomes. The completeness of social studies learning outcomes before the implementation of the action was 32%, then the completeness of the social studies learning outcomes after the implementation of the actions in the first cycle was 68%, and in the second cycle increased to 84%. The conclusion of this study is that the application of open the box games can improve social studies learning outcomes for fourth graders at SDN 2 Kalirejo for the 2020/2021 academic year.